The Use of Tacit Knowledge and School Innovation in Malaysia Secondary School - Siti Khatizah Aziz; Mohd Anuar Abdul Rahman (International Journal of Evaluation and Research in Education (IJERE), 2014)
The role of tacit knowledge in fostering organization innovation has increasingly gained interest many researchers. However, previous research dominating in the business sector. This study addresses these limitations by conceptualization in the academic setting. This study used the partial least squares (PLS) structural equation modeling (SEM) tool to test the relationship between the role of tacit knowledge among Malaysia secondary school principals and school innovation. Three types of skills used to measure tacit knowledge; cognitive skills, technical skills and social skills. As to measure school innovation, there are six latent variables; leadership, curriculum, co-curricular, student affairs, financial and structure and culture. Data from a questionnaire survey of 370 respondents from Sekolah Kebangsaan, Sekolah Jenis Kebangsaan (Cina) and Sekolah Jenis Kebangsaan (Tamil) were used to analyze the model. Partial Least Squares (PLS-SEM) was used to analyze the relationships between all the variables and found that social skill was the most significant predictor of tacit knowledge while co-curricular was the most significant predictor to school innovation and the use of tacit knowledge has a significantly smaller impact on school innovation.DOI: http://dx.doi.org/10.11591/ijere.v3i1.5329